Novel method of preparation of blue crude copper phthalocyanine having the reddish shade - Nor Ain Syuhada, Zuhaimi (2012)
Copper phthalocyanine (CuPc) is one of the most stable pigments towards light, temperature and chemicals. CuPc is prepared by reacting copper chloride, urea, phthalic anhydride and catalyst with high boiling solvent. The objective of this novel method is to obtain reddish blue shade on blue crude CuPc. For the preparation of apigment CuPc, there are two stages which the first stage is crude CuPc synthesis while second stage is the a -pigment synthesis. Blue crude CuPc has been prepared by condensation of phthalic anhydride with urea in presence of copper ions with a small amount of catalyst in inert organic solvent. Concentrated sulphuric acid has been added to the blue crude CuPc and produce a-pigment . The presence of sulphuric acid make crude and a—pigment more reddish blue shade while the presence of hydrochloric acid make crude and a—pigment more greenish blue shade. FTIR and chromometer had been used to analyze blue crude and a-pigment obtained and be compared to the standard preparation without the addition of acids. By using this novel method, the cost of material has been reduced.